PENGEMBANGAN ASESMEN KETERAMPILAN BERPIKIR KREATIF SISWA PADA MATERI LISTRIK DINAMIS - Siagian, Asister Fernando; Simamora, Aprido Bernando; Pardede, Ferri Ojak Immanuel; Sidabutar, Putri Magdalena; Simanjuntak, Dinda Zefanya (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
The purpose of this study is to develop an assessment of the creative thinking skills of Junior High School (SLTP) students in the Natural Sciences subject of Dynamic Electricity. The assessment consists of 5 essay questions about students' creative thinking skills with indicators such as fluency, flexibility, originality, and elaboration. The type of research is a development with a Four-D model consisting of 4 stages, namely define, design, develop, and disseminate. The research subjects for the assessment trial were 60 3rd grade junior high school students, namely 20 people on a limited scale and 40 people on a broad scale. The creative thinking skills assessment was validated by 3 validators, including creative thinking experts, learning experts, and science material experts (criticizing the depth and truth of the dynamic electricity science material). Experts validated the assessment in terms of content, construct, and language analyzed with Aiken V. The results of this study are assessments that have been validated and received advice from experts as validators, revised and retested until calculated with the calculation of Content Validity Ratio (CVR), Content Validity Index (CVI). The results of Aiken's Aikan V 0.75 ≤ V ≤ 1 with a very valid category, with the results obtained from the validator CVR of 1 and CVI of 1, thus the results of the validity of students' creative thinking skills questions are declared valid and can be used as an assessment of creative thinking skills.